Analysis of Motivating Factors for Visiting Wineries in the Vršac Wine Region (Vojvodina, Serbia) - Jevic, Goran; Popesku, Jovan; Jević, Jelena (Geographica Pannonica, 2020)
The paper will present the research results of motivational factors influencing wine tourists in decision making process regarding their visits to the wineries in the Vršac wine region, an area which belong to South Banat wine region according to the official regionalization and comprises the west slopes of Vršac mountains (South East Vojvodina). The aim of the paper is to analyse visitors of the Vršac wineries in order to establish components of the motivation and to define the influence they have on the decision to participate in the wine tourism in this region. The methodology of this approach entails: defining and establishing the importance of wine tourism, identifying motivating factors in wine tourism, followed by definition and analysis of the most relevant motivating factors of the wine tourist visiting the Vršac wineries, establishing the intensity of their attitudes related to certain factors and, finally, offering recommendations to the Vršac wineries management in order to create the high quality marketing mix aimed at clearly defined target markets and to position successfully in the wine tourism market. One of the conclusions is that the visitors to the Vršac wineries regard wine tasting as the most important motivating factor, followed by socializing and relaxation.